Graphene oxide-modified layered double hydroxide/chitosan nacre-mimetic scaffolds treat breast cancer metastasis-induced bone defects. (5th November 2022) - Shi, Jing-Jing; Ge, Yu-Wei; Fan, Zhang-Hao; Li, Yang; Jia, Wei-Tao; Guo, Ya-Ping
Abstract: Surgical resection of breast cancer bone metastases causes two serious consequences including large bone defects and tumor recurrence risk. Herein, nacre-mimetic graphene oxide/layered double hydroxide/chitosan (GO/LDH/CS) layered scaffolds with appropriate mechanical strengths, excellent anti-tumor and pro-osteogenesis activities were developed for the therapy of breast cancer bone metastases. The bifunctional scaffolds were constructed by the composite films layer by layer using CS as organic matrices and LDH/GO as inorganic fillings. The nacre-mimetic architecture endowed the bone scaffolds with a great compression strength, avoiding the damage of layered macropores during a therapeutic process. The modification of GO photothermal agents made the GO/LDH/CS layered scaffolds have anti-tumor function. Under near-infrared (NIR) light irradiation, the local temperature around the GO/LDH/CS scaffolds rose to 52 °C within 2 min, which was high enough to trigger tumor apoptosis via increasing caspase-3 expression. Moreover, the combined effect of GO nanosheets and Mg 2+ ions enhanced the pro-osteogenesis activity of the GO/LDH/CS layered scaffolds. After 12 weeks of post-operation, the layered macropores in the scaffolds were filled with extracellular matrix and bone tissues. Hence, the integration of nacre-mimetic architecture and biofunctional materials may be a novel approach to treat intractable disease-related bone defects. Graphical abstract: Image 1 Highlights: GO/LDH/CS layered scaffolds were constructed against breast cancer bone metastases. Nacre-mimetic architecture showed layered macropores and great compressive strength. GO photothermal agents enhanced anti-tumor activity of nacre-mimetic scaffolds. NIR-light irradiated GO/LDH/CS scaffolds induced tumor apoptosis. GO nanosheets and Mg 2+ ions promoted osteogenic differentiation of MC3T3-E1 cells.